Visualizations to support self-regulation of students' learning behaviors - Moraes, Marcia, author; Pouska, Beth, author; McKenna, Kelly, author; Folkestad, James E., author (Colorado State University. Libraries, 2018)
This study used learning analytics visualizations in the form of visual graphics of students’ spaced-retrieval practice (SRP) to support students’ reflection on their learning behavior and to learn from that exposure. Students did retrieval practice activities (RPAs) and after the last RPA, they received a visualization of their RPA attempt data and then were prompted with reflection questions. Results showed that most of the students engaged in behaviors oriented toward getting the highest score; they understood the benefits of SRP but did not engage in that behavior; and they wanted to compare their work and effort with their classmates.
218 - Marcia Moraes
School of Education, Center for the Analytics of Learning and Teaching.
Keywords: spaced-retrieval practice; learning analytics visualizations